2021
DOI: 10.3390/mining1030017
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field Analysis of Turbidity Flows Generated by Polymetallic Nodule Mining Tools

Abstract: The interest in polymetallic nodule mining has considerably increased in the last few decades. This has been largely driven by population growth and the need to move towards a green future, which requires strategic raw materials. Deep-Sea Mining (DSM) is a potential source of such key materials. While harvesting the ore from the deep sea by a Polymetallic Nodule Mining Tool (PNMT), some bed sediment is unavoidably collected. Within the PNMT, the ore is separated from the sediment, and the remaining sediment–wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…1A ). A recent modeling effort ( 17 ) did not consider the role of the vehicle’s turbulent wake and three-dimensional effects in the vicinity of the collector vehicle, which this study shows to be vital considerations. Flow conditions in the deep ocean are not quiescent, however, and a collector plume will interact with background currents.…”
Section: Introductionmentioning
confidence: 92%
“…1A ). A recent modeling effort ( 17 ) did not consider the role of the vehicle’s turbulent wake and three-dimensional effects in the vicinity of the collector vehicle, which this study shows to be vital considerations. Flow conditions in the deep ocean are not quiescent, however, and a collector plume will interact with background currents.…”
Section: Introductionmentioning
confidence: 92%
“…Firstly, the force exerted by the flow on the bed is the key parameter to be optimised in order to minimise the erosion depth. Once minimised, the amount of discarded sediment behind the collector through a discharge duct will be minimised, consequently reducing the corresponding environmental pressure [10]. Secondly, the amount of the spilling water behind the collector head must also be minimised in order to reduce the amount of suspended sediment transported directly behind the collector head.…”
Section: Discussionmentioning
confidence: 99%
“…The prediction of the evolution and fate of these plumes is central to the environmental impact assessment of deep-sea mining activities [6][7][8][9]. To this end, the characteristics of the sediment-water mixture discharged at the rear of the collector should be determined [10].…”
Section: Introductionmentioning
confidence: 99%
“…Additional numerical simulation studies for sediment plume behavior in deep-sea water columns were reported [90,91]. The ground truth of the simulation results by the environmental monitoring of larger-scale deep-sea impact experiments is required for quantitative multidisciplinary impact and risk assessments of FN mining.…”
Section: Large-scale Deep-sea Impact Experiments Scheduled and Simulation Studiesmentioning
confidence: 99%